Pengaruh Metode Aplikasi dan Konsentrasi Gibberellic Acid (GA3) terhadap Fase Pertumbuhan Vegetatif Tanaman Nanas (Ananas comosus [L.] Merr) - Maraaini, Ajeng; Widyastuti, R. A. Diana; Warganegara, Hayane Adeline; Karyanto, Agus (JURNAL AGROTROPIKA, 2024)
Increasing the production of pineapple fruit can be done by manipulating the plant using Gibberellic Acid Growth Regulatory Substance (ZPT).  The purpose of this study was to determine the effect of GA3 concentration and application method, as well as its interaction in increasing the vegetative growth of pineapple plants.  Data collection was carried out in November 2022- February 2023 at a pineapple plantation company in Central Lampung. Treatments were arranged factorial (3x2) using a randomized block design with 3 replications. The first factor was Gibberellin (A) which consisted of three levels, (A1) 0 ppm GA3, (A2) 200 ppm GA3, and (A3) 400 ppm GA3.  The second factor is the application method (B) which consists of 2 levels, namely (B1) Application on the top of the leaf (B2) Application on the bottom of the leaf. The observed variables included plant height, stem diameter, number of leaves, D-leaf length, D-leaf width, number of roots, root length, fresh weight of roots, fresh weight of plants. Homogeneity of variance between treatments was tested by Barlett's test and additivity using Tukey's test and then analysis of variance was carried out.  Separation of the mean was carried out using the least significant difference test (LSD) at the 5% level. The results showed that 400 ppm GA3 was better than the control in affecting plant fresh weight with a difference of 630,7 g, the treatment of the application method on the leaves was better than the bottom leaf in affecting plant fresh weight with a difference 201,4 g. Treatment with a concentration of 40 ppm using the leaf application method was better than the control treatment. It is suggested to do further research related to the effect of giving GA3 on the generative phase of pineapple plants.Keywords : Gibberellic Acid, application method, pinneaple